Planaridade em grafos: o teorema de Kuratowski - Santos, Emanoel Lázaro de Santana (2017)
The present dissertation aims to introduce the basic concepts of graph theory to explore the concept of planarity and present a beautiful theorem connected to this theme. Graph theory is a very effective tool for solving problems involving several areas of knowledge. Some of these problems are related to planarity of graphs. Thus, this work presents Kuratowski’s theorem, with the beauty of its demonstration, which provides a necessary and sufficient condition for a graph to be planar, observing if it contains a specific type of subgraph related to complete and split graphs.